Decellularization of Dense Regular Connective Tissue-Cellular and Molecular Modification with Applications in Regenerative Medicine - Data, Krzysztof; Kulus, Magdalena; Ziemak, Hanna; Chwarzyński, Mikołaj; Piotrowska-Kempisty, Hanna; Bukowska, Dorota; Antosik, Paweł; Mozdziak, Paul; Kempisty, Bartosz (Cells, 2023)
Healing of dense regular connective tissue, due to a high fiber-to-cell ratio and low metabolic activity and regeneration potential, frequently requires surgical implantation or reconstruction with high risk of reinjury. An alternative to synthetic implants is using bioscaffolds obtained through decellularization, a process where the aim is to extract cells from the tissue while preserving the tissue-specific native molecular structure of the ECM. Proteins, lipids, nucleic acids and other various extracellular molecules are largely involved in differentiation, proliferation, vascularization and collagen fibers deposit, making them the crucial processes in tissue regeneration. Because of the multiple possible forms of cell extraction, there is no standardized protocol in dense regular connective tissue (DRCT). Many modifications of the structure, shape and composition of the bioscaffold have also been described to improve the therapeutic result following the implantation of decellularized connective tissue. The available data provide a valuable source of crucial information. However, the wide spectrum of decellularization makes it important to understand the key aspects of bioscaffolds relative to their potential use in tissue regeneration.
Keywords: buněčná diferenciace; lidé; patologická angiogeneze; Humans; Embryo Implantation; Regenerative Medicine; regenerativní lékařství; nukleové kyseliny; Neovascularization, Pathologic; implantace embrya; Cell Differentiation; Nucleic Acids